Evaluation of the role of US dollar as a global reserve currency - Gál, Dávid; Dudzich, Viktar; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
There is an ongoing debate whether the US dollar can still remain a reserve currency and maintain its dominance in the global economy. This matters since dethroning of the currency could significantly impact global power dynamics and the United States themselves. The thesis will therefore try to answer if such an event is underway or could occur in the near future. The evaluation is based on examining quantitative indicators of its dominance and spotting any trend shifts in the data which could support or refute this fact. Drawing primarily from scholarly literature and empirical evidence from the IMF and the Bank for International Settlements, the research reveals that the US dollar maintains unparalleled dominance based on various indicators. However, a closer examination of prevailing trends introduces ambiguity; while there is an upward trend in areas such as international trade and debt denomination, other indicators suggest a declining role (e.g., declining volumes of forex transactions involving US dollars and a diminishing share of US dollars in central bank reserve currency holdings). Despite these negative trends, their significance appears gradual, and they do not forecast an imminent dethronement of the US dollar in the foreseeable future.
Vedoucí práce: Viktar Dudzich
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses